Intelligent Interaction Honeypots for Threat Hunting within the Internet of Things (Journal of The Colloquium for Information Systems Security Education, 2022)
As the Internet of Things (IoT) grows exponentially, security is falling farther and farther behind. Several new initiatives show promise for expanding the privacy and security around these devices in the future. But what about the billions of devices already out there in the wild? Security researchers are responsible for developing the tools and procedures for discovering these devices quickly, understanding the risks they bring with them, and developing tools to mitigate those risks to more manageable levels. Honeypots and honeynets have traditionally supported this work in traditional IT. However, the challenges faced by the highly distributed, incredibly heterogeneous Internet of Things make deploying such tools difficult and costly. Recent research in honeypot architectures explicitly designed for the chaotic nature of the IoT ecosystem brings a new sense of hope that may lead to significant improvements in IoT security. There is still much work to do, but research continues. IoT cybersecurity experts and threat hunters are developing strategies for securing this new frontier of technology. This study will lay the foundations for an intelligent and highly interactive honeypot solution that can scale with the researchers' requirements, providing a much-needed framework for deploying targeted IoT honeypots.
Keywords: Internet of Things; IoT; threat hunting; cybersecurity; honeypot